Peningkatan Hardskill Siswa SMK NU 1 Islamiyah Kramat melalui Pelatihan Pembuatan Alat Ukur Suhu Ruang Berbasis Mikrokontroler - Khakim, Lukmanul; Budihartono, Eko; Sutanto, Achmad; Nurohim, Nurohim (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2025)
Background: The development of microcontrollers in the industrial world is progressing rapidly. However, students, as one of the successors of technological advancement, still lack knowledge related to microcontroller-based technology. Therefore, it is essential to introduce this technology to students, especially at SMK NU 1 Islamiyah Kramat, to help them understand and expand their knowledge of microcontroller-based technology as an effort to enhance their hard skills in the field of electronic engineering. Methods: This community service activity (PKM) was conducted at SMK NU 1 Islamiyah Kramat and involved 29 students from grades X and XI in the Computer and Network Engineering department. The PKM implementation team from Poltek Harber consisted of 4 lecturers and 2 students from the D-III Computer Engineering program. The PKM activity began with a presentation on microcontroller-related materials, followed by training and hands-on practice in creating a temperature measurement project, as well as pre-tests and post-tests. Results: After the PKM activity was conducted and evaluated, there was an improvement in students' understanding of using and creating microcontroller-based projects. This was evident from the pre-test and post-test results, where the high-category pre-test score increased from 61,1% to 79,8%, reflecting a 18,7% improvement. Conclusions: From the PKM activity conducted at SMK NU 1 Islamiyah Kramat, it can be concluded that efforts to enhance students' hard skills in understanding and practicing microcontroller-based technology have been optimal. This conclusion is supported by the pre-test and post-test results, which showed a significant 18,7% improvement.